ANALISIS PRODUKTIVITAS DAN FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKSI CABAI BESAR - Antonius Wuntas; I Made Tamba; I Made Budiasa (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2023)
Chilli is one of the horticulthyral commodities that receives more attention to be developed. This study aims to analyze the productivity and factors that affect the production of large chili peppers in Batunya Village. The location of this study was conducted in Batunya Village, Baturiti District, Tabanan Regency. This research was conducted from March to June 2022.Data qualitative and quantitative data. The data analysis used was a multiple regression of Cobb Dounglas with SPSS version 22 tools. The samples in this study 38 people Raspocndent. The results showed that the average productivity of large chilies in Batunya Village, Baturiti District, Tabanan Regency was 45,96 kg / ha. Production factors, namely land area, seeds, urea fertilizer, organic fertilizer, and labor together influence the factors affecting the production of large chili farmers. However, the most influential factor in the production of large chili farming businesses in Batunya Village, Baturiti District, Tabanan Regency is the land area. However, it can be recommended to farmers in Batunya Village, Baturiti District, Tabanan Regency so that large chili farming businesses continue to be maintained and further improved, because the agriculture carried out can provide quite high productivity